Agrarism – the forgotten world of norms and values - Fedyszak-Radziejowska, Barbara (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2012)
The article brings back to our memory the ideas of agrarism and the fates of political formation that tried to introduce these ideas into the public and political life of Poland after the Second World War. However, the ideas of agrarism and the political formation implementing its goals and values suffered a defeat in the clash with the doctrine binding in People's Poland. The author describes the way in which this important experience of Polish peasants was erased from the tradition and memory of the Polish nation. She points to the intentional character of the discontinuation of agraristic tradition and the role played in this process by reprisals of the Stalinist period. She shows the contemporary, complex consequences of the ennoblement of socialist solutions and the social costs of the marginalization of democratic, solidary solutions of agrarism that lost in 1947.
Keywords: agrarism; tradition; national memory; inter-generational transimission; public discourse